2021
DOI: 10.1177/23247096211058489
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pseudoprogression in Hepatocellular Carcinoma Treated With Atezolizumab Plus Bevacizumab

Abstract: A 74-year-old man was diagnosed with hepatocellular carcinoma. The tumor in the liver showed a complete response after transcatheter arterial chemoembolization, but lung, bone, and lymph node metastases were observed, so treatment with atezolizumab plus bevacizumab was initiated. After administration, the scans showed tumor growth, but after continuous administration of atezolizumab plus bevacizumab, the tumors finally reduced in size and showed a partial response. The transient growth of the tumors was consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…A systematic review and meta-analysis reported that the overall incidence of pseudoprogression was 6.0% in clinical trials of cancer patients on ICIs (5). However, HCC pseudoprogression is rare (6); indeed, to our knowledge, there have only been two previous reports (7,8). This is the first report of pseudoprogression of an HCC accompanied by main portal vein and right ventricular invasion followed by a dramatic response in a patient on atezolizumab plus bevacizumab.…”
Section: Discussionmentioning
confidence: 96%
“…A systematic review and meta-analysis reported that the overall incidence of pseudoprogression was 6.0% in clinical trials of cancer patients on ICIs (5). However, HCC pseudoprogression is rare (6); indeed, to our knowledge, there have only been two previous reports (7,8). This is the first report of pseudoprogression of an HCC accompanied by main portal vein and right ventricular invasion followed by a dramatic response in a patient on atezolizumab plus bevacizumab.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the number of cases of pseudoprogression should be increased accordingly. To our knowledge, however, there have been only five reports concerning pseudoprogression in HCC; there thus remains a need to improve the broader understanding of pseudoprogression and its diagnosis (7,(12)(13)(14)(15). Rocha et al described a patient with stage IV squamous cell lung cancer with pseudoprogression, and a pathological analysis of liver lesions revealed extensive areas of necrosis, the absence of viable tumor cells, and the presence of lymph histiocytic infiltrate (16).…”
Section: Discussionmentioning
confidence: 99%
“…did not report pseudoprogression in the Korean cohort, 58 it is worth noting that two clinical cases have documented this phenomenon in the context of HCC 59,60 . Thus, the emergence of pseudoprogression introduces an additional confounding factor necessitating in‐depth scrutiny 61 …”
Section: Swot Analysis Of Systemic Treatment In Hcc Fieldmentioning
confidence: 99%
“…59,60 Thus, the emergence of pseudoprogression introduces an additional confounding factor necessitating in-depth scrutiny. 61 In the context of immunotherapy, the potential impact of antibiotics and etiology on treatment efficacy has been a subject of concern, representing an unmet need. While both of these topics are of significant interest, the authors have chosen not to include data on antibiotics and HCC in the present review as the available information is considered too preliminary.…”
Section: Development Of Resistancementioning
confidence: 99%